Effectiveness of Educational Programme Regarding Febrile Seizures Management Among Mothers - Mujawar, Roja Rustum; Naregal, Prakash M.; Shinde, Mahadeo B (International Journal of Psychosocial Rehabilitation, 2020)
Background: Febrile seizure is neurologic condition of childhood triggered by increase in the body temperature and these seizures are associated with fever but excluding those related to Central Nervous System infections. Globally 3% to 8% of children are affected by febrile convulsions. This study carried out to assess the mothers’ knowledge and effectiveness of educational programme on management of febrile seizures. Methods: An evaluative research approach was used to accomplish the objectives of the study. One group pre-test post-test design was used. Data collected from 50 mothers of children’s age less than five years hospitalized were through purposive sampling technique. Self structured knowledge questionnaire was administered to assess the pre-test knowledge of the mothers on 1st Day and followed by educational programme on knowledge of management of febrile seizures among mothers was conducted. Post-test was conducted on 8th day. Descriptive and inferential statistics were used for data analysis.Results: The mean , standard deviation of pre-test knowledge scores of mothers on management of febrile seizures was 9.4 + 2.9, which has increased in post-test to 20.7+3.4 and paired ‘t’ test value was 17.671 and p value was <0.0001 hence the educational programme was effective in increasing the mothers knowledge. Conclusion- The study concluded that there was an improvement in mothers knowledge regarding management of febrile seizures in underfive children and also it will help in preventing complications.